Psychometric characteristics of the of COVID Stress Scales-Arabic version (CSS-Arabic) in Egyptian and Saudi university students - Abbady, Adel S. (Middle East Curr Psychiatry, 2021)
BACKGROUND: Mental health sufferings due to the COVID-19 pandemic were reported in many countries worldwide. However, there is a lack of a validated Arabic tool to measure stress related to this pandemic in the Arab countries. This study aims to translate into Arabic and measure the psychometric characteristics of the previously developed English COVID Stress Scales (CSS). Using a forward-backward translation, the CSS was translated into Arabic and 22 jurors assessed its content validity. An online-based survey was carried out among 1080 university students (Egyptian and Saudi) to assess internal consistency and validity of the Arabic version (CSS-Arabic) using Cronbach’s α and factor analysis. RESULTS: The content validity indices of the scale were 0.943 and 0.932 for both relevance and clarity. The internal consistency of the total CSS-Arabic was satisfactory (with α = 0.94) within the acceptable range for different subscales. Confirmatory factor analysis reveals 5-factor model with 36 retained items similar to the original English CSS. CONCLUSIONS: CSS-Arabic is a reliable and valid self-reporting tool for screening of stress due to COVID-19 among the university students. Further work should be done by healthcare providers to assess the magnitude of the stress during the COVID-19 pandemic. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s43045-021-00095-8.